The Strain Rate Dependent Material Behavior of S-GFRP Extracted from GLARE - Gerlach, R; Siviour, C; Wiegand, J; Petrinic, N (2013)
S-Glass fiber reinforced epoxy (S-GFRP) extracted from GLARE has been experimentally characterized at three distinct strain-rates (5 × 10 -4 s-1, 10 s-1, and c.a. 2000 s-1) and in four loading directions (0°, 90°, and 45° to the fiber direction and in the through-thickness direction). A novel specimen clamping mechanism was developed and full-field optical strain measurement was applied. With the aid of these techniques, a significant increase in failure-strength and apparent elastic modulus in all loading directions, particularly in fiber direction, was observed with an increased strain-rate; strain to failure increased in the fiber direction and decreased in all other loading directions. © 2013 Copyright Taylor and Francis Group, LLC.